Obstacles Encountered by the English Department Students in Learning English: Case Study of Universitas Negeri Malang - Emynorane, Ralaivao Hanginiaina; Arrive, Jean Tsitaire (LPTNU Sumenep, 2024)
The objective of this study is to outline the obstacles encountered by the English department students in Learning English language at the English Literature Department in Universitas Negeri Malang. This study uses a qualitative method with a case study design and data were collected through interviews techniques and literature reviews. The collected data were organized, interpreted, and deeply analysed in order to develop concepts and abstraction of the research findings. Data credibility was checked through member checking and referential adequacy. The results of this study unveiled that students experience lack of self-confidence in speaking English and lack of extracurricular activities provided by the faculty to improve students’ skills. For this reason, the following suggestions are very necessary, first, for the English Department students, they are encouraged to increase their self-confidence and to actively participate during the academic activities. Second, for the English Literature Department, to increase the number of extracurricular activities and to establish more cooperation with foreign institutions. Third, for the lecturers, they should always use English language during the academic activities and to provide more motivation to students to keep on working hard.